Human Platelets Take up Anti-VEGF Agents - B. Sobolewska; B. Fehrenbacher; P. Münzer; H. Kalbacher; S. Geue; Konstantinos Stellos; M. Schaller; F. Ziemssen (Journal of Ophthalmology)
Purpose. Growing evidence suggests different systemic exposure of anti-vascular endothelial growth factor (anti-VEGF) agents with repeated intravitreal application. Since the penetration of anti-VEGF agents through vascular barrier was reported, the interaction of anti-VEGF with nonresident platelets has become a topic of interest. The purpose of this study was to evaluate, with the help of visualization techniques, whether platelets take up the anti-VEGF agents ranibizumab, aflibercept, and bevacizumab. Methods. The uptake of anti-VEGF agents with or without VEGF treatment was investigated using immunofluorescence and immunogold staining in human platelets. The role of actin filaments and clathrin-coated vesicles in the transport of ranibizumab, aflibercept, and bevacizumab was evaluated by two pharmacologic inhibitors: staurosporine (protein kinase C inhibitor) and cytochalasin D. Results. All three anti-VEGF agents were taken up by platelets and colocalized with VEGF. Ranibizumab and aflibercept were mainly detected in alpha-granules; however, bevacizumab was equally localized in alpha-granules and in platelet vesicles. Both staurosporine and cytochalasin D completely inhibited the uptake of aflibercept into platelets. Both pharmacological inhibitors also decreased the transport of ranibizumab and bevacizumab into platelets. Bevacizumab was significantly more frequently colocalized within clathrin-coated vesicles than ranibizumab and aflibercept. Conclusion. All three anti-VEGF agents are taken up by platelets and internalized in alpha-granules, which may result in a higher local exposure of anti-VEGF after the activation of platelets, potentially contributing to arterial thromboembolic events. Clathrin-coated vesicles seem to be more prominent in the transport of bevacizumab than ranibizumab and aflibercept. Nevertheless, whether the different localization and transport of bevacizumab are truly related to specific differences of receptor-mediated endocytosis has to be revealed by further research.